IoMT Device Performance in Chronic Disease Management: A Mixed-Methods Clinical Validation in a Public LMIC Healthcare System - Silva Atencio, Gabriel (PT. Teknologi Futuristik Indonesia, 2026)
The Internet of Medical Things (IoMT) holds promise for chronic disease management, yet evidence from low- and middle-income countries (LMICs) remains scarce, limiting equitable digital health policy development. No previous studies have clinically validated IoMT device performance against electronic health records (EHRs) within Central American public healthcare systems, leaving assumptions about consumer device adequacy untested in resource-constrained settings. This mixed-methods study evaluated IoMT implementation in Costa Rica's Caja Costarricense de Seguro Social (CCSS) system, examining (1) diagnostic accuracy stratification between consumer and clinical-grade devices, (2) healthcare system interoperability challenges, and (3) cost implications of false alerts. Among 50 chronic disease patients, consumer wearables demonstrated 43% sensitivity for cardiac event detection versus 92% for clinical-grade devices (p<0.001). Only 25% of consumer devices integrated with CCSS EHRs versus 100% of clinical-grade devices, requiring 22 minutes of manual data entry per encounter. False positives occurred in 12% of consumer-device alerts, costing an average of 35 per event. Qualitative analysis revealed that 45% of participants overestimated consumer-device diagnostic capabilities. These findings challenge assumptions about universal consumer-technology applicability in LMICs and support tiered implementation frameworks. As Costa Rica prepares for its Digital Health Act 2025, evidence-based device categorization, interoperability investments, and patient education are essential for equitable IoMT integration.